BLOODSTREAM INFECTION IN PATIENTS WITH CENTRAL VENOUS CATHETER HOSPITALIZED IN AN INTENSIVE CARE UNIT (Fiep Bulletin - online, 2016)
INTRODUCTION: The intensive care unit (ICU) is a complex structure that offers advanced support of life to potentially serious or unbalanced patients. These need continuous monitoring and become exposed to a series of risks that can contribute to worsen even more their general condition, facilitating the installation of infectious processes. Thus, the invasive procedures are constantly performed in the treatment to patients hospitalized in the ICU, and the central venous catheter is indispensable to help to help improve the general condition of the patient (LIMA; ANDRADE; HAAS; 2007). For Marino (2008, p. 105) “The term central venous catheter refers to the catheter which is projected for the cannulation of the da subclavian vein, the internal jugular vein or the femoral vein”. OBJECTIVES: To evaluate the incidence and the factors that offer risk of bloodstream infection in patients with central venous catheter double lumen (CVC). MATERIALS AND METHODS: It is a field, documental, exploratory, and descriptive of quantitative approach research. RESULTS AND DISCUSSIONS: Among the 20 patients observed only 1 (5%) has had the infection and was affected by the microorganism Staphylococcus epidermidis. Out of the 20(100%) patients, 11(55%) didn't show late complications, but the others had: 7(35%) hyperemia, 1(5%) worse lab exams and 1(5%) pneumothorax. Related to complications in the subclavian insertion, pneumothorax was observed as an immediate complication 1(4,76%) and hyperemia and worse lab exams as late complications 9(42,85%). In the insertion in the jugular there weren't immediate complications, however, there were late complications: 4(66,66%) hyperemia. With regard to the preventive measures, the professionals from the night shift were the ones who adhered most to hand sanitization, and disinfection of connectors, whereas the bandage change was more often performed by the afternoon and night shift professionals. CONCLUSION: In conclusion, the use of CVC can lead to a high level of infection and complications, so educational programs that aim at the application of preventive measures are necessary.
Keywords: Infection; bloodstream; central venous catheter.